Soft-power internationalism competing for cultural influence in the 21st-century global order - Baykurt, Burcu; De Gracia, Victoria (Columbia University Press, 2021)
"The term "soft power" was coined in 1990 to foreground a capacity in statecraft analogous to military might and economic coercion: getting others to want what you want. Emphasizing the magnetism of values, culture, and communication, this concept promised a future in which cultural institutes, development aid, public diplomacy, and trade policies replaced nuclear standoffs. From its origins in an attempt to envision a United States-led liberal international order for a post-Cold War world, it soon made its way to the foreign policy toolkits of emerging powers looking to project their own influence. This book is a global comparative history of how soft power came to define the interregnum between the celebration of global capitalism in the 1990s and the recent resurgence of nationalism and authoritarianism. It brings together case studies from the European Union, China, Brazil, Turkey, and the United States, examining the genealogy of soft power in the Euro-Atlantic and its evolution in the hands of other states seeking to counter U.S. hegemony by nonmilitaristic means. Contributors detail how global and regional powers created a variety of new ways of conducting foreign policy, sometimes to build new solidarities outside Western colonial legacies and sometimes with more self-interested purposes. Offering a critical history of soft power as an intellectual project as well as a diplomatic practice, Soft-Power Internationalism provides new perspectives on the potential and limits of a multilateral liberal global order"--